Preparation method and application of selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery diaphragm
By co-doping separator of selenium nitrogen to carbon-loaded molybdenum-based material, the shuttle effect problem caused by the dissolution of polysulfides in lithium sulfur batteries is solved, the cycle stability and rate performance of the battery is significantly improved, and efficient sulfur oxidation is achieved Reduction reaction.
Patent Information
- Application Number
- CN202411579255.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-07
AI Technical Summary
In practical applications, lithium-sulfur batteries face shuttle effects caused by polysulfide dissolution, resulting in loss of active materials and shortening of battery cycle life. The existing modification strategies are difficult to enhance the adsorption site of polar materials and change the kinetics of polysulfide conversion. process.
Using selenium-nitrogen co-doped carbon-supported molybdenum-based materials as electrocatalysts, nanorod-like catalysts are prepared by raw materials such as MoO3, polyvinylpyrrolidone, metal zinc salt and 2-methylimidazole, and selenium-nitrogen co-doped carbon-supported by annealing and heat treatment. Molybdenum carbide material is mixed with PVDF binder to apply on a commercial polypropylene separator to form a modified battery separator.
Effectively resist polysulfides, accelerate the redox reaction kinetics of sulfur, inhibit the shuttle effect of polysulfides, significantly improve the cycle stability and rate performance of lithium-sulfur batteries, and the discharge specific capacity reaches 572.1 mAh g- 1, and the capacity decay rate of each turn of 700 turns cycles at 1 C current rate is only 0.055%.
Smart Images

Figure CN119231090A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-sulfur batteries, and in particular relates to a preparation method and application of a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator. Background Art
[0002] To achieve the goal of carbon neutrality, electric vehicles (EVs) and large-scale energy storage systems (ESSs) have been rapidly developed. For many years, lithium-ion batteries (LIBs) have been widely used in these fields as a green power source. -1 ) and energy density (2600 Wh kg -1 Lithium-sulfur (Li-S) batteries have attracted much attention from researchers and are considered to be one of the most promising high-energy storage systems. The rechargeability of these batteries mainly relies on the presence of long or short sulfur chains (from S 8 2- To S 2 2- ) redox transformation of polysulfides (LiPSs). A major problem they face in practical applications is the "shuttle effect" caused by the dissolution of polysulfides in the electrolyte. These soluble polysulfides migrate unhindered to the lithium anode through the porous separator, resulting in active material loss and shortened battery cycle life. In the past few decades, many immobilization strategies have been developed to address this problem, such as composite cathodes, polysulfide adsorption, solid electrolytes, and electrolyte additives. Although these strategies prevent the escape of soluble polysulfides from the cathode to a certain extent, there is also increasing evidence that the uneven deposition of lithium ions on the anode side can lead to dendrite growth and battery short circuits. In addition, the "dead sulfur" generated near the commercial polypropylene (PP) separator during the charge and discharge cycle can also cause serious problems. Therefore, some researchers have proposed to modify the traditional separator by coating it with a layer of functional materials. Common modification materials based on physical barriers and chemical adsorption include carbon nanotubes, graphene, nitrides, sulfides, etc., which are coated on the surface of traditional separators to prevent soluble polysulfides from escaping from the cathode. However, it is difficult to enhance the adsorption sites of polar materials through modification strategies, and it is also difficult to change the slow kinetics of polysulfide conversion. Therefore, the development of new modified materials with excellent chemical adsorption properties and high electrolytic activity remains an important issue. Summary of the invention
[0003] In order to solve the above problems, the purpose of the present invention is to provide a preparation method and application of a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator, which is used to develop a controllable preparation technology of selenium-nitrogen co-doped molybdenum-based material electrocatalyst to accelerate the redox reaction kinetics of sulfur and inhibit the "shuttle effect" of polysulfides.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator comprises the following steps: S1: MoO 3 , polyvinyl pyrrolidone and metal zinc salt are dissolved in anhydrous methanol, and stirred thoroughly to obtain a mixed solution; S2: Dissolve 2-methylimidazole in anhydrous methanol and stir thoroughly to obtain a clear solution; S3: The mixed solution of S1 and the clarified solution of S2 are mixed and stirred to obtain a precipitate, and the precipitate is washed and dried to obtain MoO 3 @ZIF-8 precursor material; S4: To MoO 3 @ZIF-8 precursor material is annealed to obtain nitrogen-doped carbon-loaded molybdenum carbide material; S5: mixing the nitrogen-doped carbon-loaded molybdenum carbide material and selenium powder and subjecting them to heat treatment to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum carbide material; S6: Mix the selenium-nitrogen co-doped carbon-loaded molybdenum carbide material with the PVDF binder, add it into N-methylpyrrolidone solvent, stir evenly to form a slurry, apply the slurry on the surface of a commercial polypropylene diaphragm, and obtain a modified battery diaphragm after drying.
[0005] Preferably, the metal zinc salt in step S1 is zinc nitrate, zinc chloride or zinc sulfate; MoO 3 The mass ratio of MoO to polyvinyl pyrrolidone is 1:10~10:1; 3 The mass ratio of polyvinyl pyrrolidone to metal zinc salt is 1:10~10:1; the mass ratio of polyvinyl pyrrolidone to metal zinc salt is 1:5~5:1; MoO 3 The concentration of is 0.01~0.1 mmol / mL; the concentration of polyvinyl pyrrolidone is 0.0001~0.001 mmol / mL; the concentration of metal zinc salt is 0.01~0.1 mmol / mL.
[0006] Preferably, the concentration of 2-methylimidazole in methanol in step S2 is 0.1-1 mmol / mL.
[0007] Preferably, in step S3, the volume ratio of the S1 mixed solution to the S2 clarified solution is 2:1-1:2; the stirring time is 20-45 min, and the washing is performed 3-5 times with water and ethanol.
[0008] As a preferred embodiment, in step S4, MoO 3 @ZIF-8 precursor material annealing atmosphere is N 2 or Ar / H 2The mixed gas has an annealing temperature of 600-900 °C and an annealing time of 1-3 h.
[0009] Preferably, in step 5, the mass ratio of nitrogen-doped carbon-loaded molybdenum carbide and selenium powder is mixed in a range of 1:10 to 10:1.
[0010] Preferably, the heat treatment atmosphere in step S5 is N 2 or Ar / H 2 Mixed gas, heat treatment time is 1~5h; heat treatment temperature is 300~700 °C.
[0011] Preferably, in step S6, the selenium-nitrogen co-doped carbon-loaded molybdenum carbide material is 15-25 mg, the PVDF binder is 2-3 mg, and the N-methylpyrrolidone solvent is 90-110 mg. The slurry is coated on the surface of a commercial polypropylene diaphragm with a thickness of 10-100 μm.
[0012] Preferably, the drying temperature in step S6 is 40-90 °C and the drying time is 9-18 h.
[0013] Selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator can be used to make batteries.
[0014] The selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator prepared according to the above method has a catalyst in the shape of nanorods, in which the elements are evenly doped. The synergistic effect between the multiple active components enables the electrocatalyst to effectively resist polysulfides, accelerate the redox reaction kinetics of sulfur, and inhibit the "shuttle effect" of polysulfides.
[0015] As a preferred embodiment, when the prepared selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is assembled into a lithium-sulfur battery, the assembled lithium-sulfur battery exhibits excellent performance, such as the discharge specific capacity at the rate of 0.2 C and 5 C is 1156.0 and 572.1 mAh g, respectively. -1 . And the capacity decay rate per cycle after 700 cycles at a current rate of 1 C is only 0.055%.
[0016] Adjusting the electronic structure of catalytic materials through various strategies, such as heteroatom doping and defect engineering, can effectively improve the chemical reaction and catalytic activity. Recently, Mo-based materials, due to their adjustable crystal structure, adjustable composition and variable valence of Mo, enable them to interact strongly with soluble polysulfides through various mechanisms to inhibit the "shuttle effect". In addition, Mo-based materials are also lithiophilic, which helps to inhibit the formation of lithium dendrites on the anode and extend the cycle life of lithium-sulfur batteries. At the same time, we selected selenium as a "composite accelerator" to improve the kinetics of sulfur redox reactions. Selenium doping is expected to further enhance the catalytic effect of the material on polysulfides.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a preparation method and application of a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator. Due to the synergistic effect between the multiple active components of the catalyst, it can effectively resist polysulfides, accelerate the kinetics of sulfur redox reactions, and inhibit the "shuttle effect" of polysulfides. The battery assembled with the catalyst-modified separator can still achieve a discharge capacity of 572.1 mAh g at a current rate of 5 C. -1 , and also exhibits excellent long-term cycle stability.
[0018] The present invention also discloses a method for preparing the above-mentioned selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator, wherein MoO 3 , polyvinyl pyrrolidone, hexahydrate zinc nitrate and 2-methylimidazole as raw materials, can realize the controllable preparation of selenium-nitrogen co-doped carbon-supported molybdenum-based electrocatalyst with specific composition and its modified diaphragm. In addition, the method has simple process, low production cost and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The X-ray diffraction pattern of the selenium-nitrogen co-doped carbon-supported molybdenum-based catalyst prepared in Example 1; Figure 2 This is a scanning electron microscope image of the selenium-nitrogen co-doped carbon-supported molybdenum-based catalyst prepared in Example 1; Figure 3 The physical properties of the selenium-nitrogen co-doped carbon-supported molybdenum-based lithium-sulfur battery separator prepared in Example 1; Figure 4 The long cycle performance of the lithium-sulfur battery assembled with the selenium-nitrogen co-doped carbon-supported molybdenum-based lithium-sulfur battery separator prepared in Example 1; Figure 5 The rate performance of the lithium-sulfur battery assembled with the selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator prepared in Example 1. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0021] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0022] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0023] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0024] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0025] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0026] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio. Example
[0027] A preparation method and application of a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator, comprising the following steps: S1: 200 mg MoO 3 , 1 g of polyvinyl pyrrolidone (PVP) and 5 mmol of zinc nitrate hexahydrate (1487.45 mg) were mixed in 60 mL of anhydrous methanol and stirred thoroughly to obtain a mixed solution.
[0028] S2: Dissolve 40 mmol of 2-methylimidazole in 60 mL of anhydrous methanol and stir thoroughly to obtain a clear solution.
[0029] S3: The mixed solution was mixed with the clear solution, and stirred for 30 min to obtain a precipitate, which was collected by centrifugation, washed with water and ethanol for 3 times, and vacuum dried to obtain MoO 3 @ZIF-8 precursor materials.
[0030] S4: To MoO 3 @ZIF-8 in Ar / H 2 The nitrogen-doped carbon-loaded molybdenum carbide material was obtained by annealing at 800 °C for 2 h in a (10%) atmosphere.
[0031] S5: Nitrogen-doped carbon-supported molybdenum carbide material and selenium powder (mass ratio = 10:1) were heated in an Ar / H 2 After heating at 600 °C for 4 h in a (10%) atmosphere, selenium and nitrogen co-doped carbon-supported molybdenum carbide material was obtained.
[0032] S6: Take 20 mg of selenium-nitrogen co-doped carbon-loaded molybdenum carbide material and mix it with 2.3 mg of PVDF binder, then add it into 100 mg of N-methylpyrrolidone (NMP) solvent and stir evenly to form a slurry. The slurry is coated on the surface of a commercial polypropylene (PP) diaphragm with a thickness of 20 μm. After drying at 60 °C for 12 h, a modified battery diaphragm is obtained.
[0033] The modified diaphragm was assembled into a lithium-sulfur battery and electrochemically tested using the following method: (1) Sulfur powder and Super C were mixed in a mass ratio of 7:3 and ground for 30 min. The mixture was then placed in an oven at 155 °C for 12 h. After cooling, the sulfur-carbon cathode material was obtained.
[0034] (2) The sulfur-carbon cathode material, conductive carbon, and PVDF binder were mixed and ground evenly in a mass ratio of 8:1:1, and the slurry was coated on the surface of the carbon-coated aluminum foil. After vacuum drying at 60 °C, it was cut into discs with a diameter of 10 mm to obtain sulfur-carbon electrodes.
[0035] (3) Assemble a button cell in an argon-filled glove box, wherein the positive electrode is a sulfur-carbon electrode, the negative electrode is metallic lithium, the separator is the selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator of the present invention, and the electrolyte is composed of: 1 mol / L lithium bistrifluoromethylsulfonyl imide and 2 wt% lithium nitrate; the solvent is a mixture of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1.
[0036] Figure 1The X-ray diffraction pattern of the selenium-nitrogen co-doped carbon-supported molybdenum-based electrocatalyst prepared in Example 1 is shown. From the X-ray diffraction pattern of the product, it can be seen that the synthesized product is MoC, which has high phase purity and is highly consistent with the standard card JCPDF No.65-3558 of MoC. The structure is hexagonal, the space group is P63 / mmc, a=3.013Å, and c=14.640Å.
[0037] Figure 2 The figure shows a scanning electron microscope image of the selenium-nitrogen co-doped carbon-supported molybdenum-based electrocatalyst prepared in Example 1. The scanning electron microscope image shows that the catalyst is in the shape of a nanorod with a diameter of about 200 nm.
[0038] Figure 3 The figure shows the physical properties of the selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator prepared in Example 1. After the modified separator is folded and restored, the modified material does not fall off, which indicates that the modified separator has good physical properties.
[0039] Figure 4 The long cycle performance of the lithium-sulfur battery assembled with the selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator prepared in Example 1 is shown, and the long cycle performance of the lithium-sulfur battery assembled with the modified separator at 1 C, and its initial discharge specific capacity is 941.9 mAh g -1 After 700 cycles, it still maintains 575.4 mAh g -1 The capacity decay rate per cycle is only 0.055%.
[0040] Figure 5 The figure shows the rate performance of the lithium-sulfur battery assembled with the selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator prepared in Example 1. The lithium-sulfur battery assembled with the modified separator has excellent rate performance and reversibility. The discharge specific capacity at 0.2, 0.5, 1, 2, 3, and 5 C is 1156.0 mAh g -1 、875.7 mAh g -1 、785.9 mAh g -1 、708.7 mAh g -1 、640.7 mAh g -1 、571.4 mAh g -1 When it returns to 0.2 C, the discharge capacity is still 928.0 mAh g -1 , showing excellent redox reaction reversibility. Example
[0041] According to the method of Example 1, except that the metal zinc salt in step (1) is zinc chloride, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained. Example
[0042] According to the method of Example 1, except that the metal zinc salt in step (1) is zinc sulfate, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained. Example
[0043] The method of Example 1 is followed, except that in step (1) the MoO 3 The mass ratio of the selenium and nitrogen to PVP is 1:10, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator. Example
[0044] The method of Example 1 is followed, except that in step (1) the MoO 3 The mass ratio of the selenium and nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is 1:1, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator. Example
[0045] The method of Example 1 is followed, except that in step (1) the MoO 3 The mass ratio of the selenium and nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is 5:1, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator. Example
[0046] The method of Example 1 is followed, except that in step (1) the MoO 3 The mass ratio of the selenium and nitrogen to PVP is 10:1, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator. Example
[0047] The method of Example 1 is followed, except that in step (1) the MoO 3 The mass ratio of the selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is 1:10, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator. Example
[0048] The method of Example 1 is followed, except that in step (1) the MoO 3 The mass ratio of the selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is 1:5, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0049] Embodiment 10: The method of Example 1 is followed, except that in step (1) the MoO 3The mass ratio of the selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is 1:1, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0050] Embodiment 11: The method of Example 1 is followed, except that in step (1) the MoO 3 The mass ratio of the selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is 5:1, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0051] Embodiment 12: The method of Example 1 is followed, except that in step (1) the MoO 3 The mass ratio of the selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is 10:1, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0052] Embodiment 13: According to the method of Example 1, except that the mass ratio of PVP to metal zinc salt in step (1) is 1:5, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0053] Embodiment 14: According to the method of Example 1, except that the mass ratio of PVP to metal zinc salt in step (1) is 1:1, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0054] Embodiment 15: According to the method of Example 1, except that the mass ratio of PVP to metal zinc salt in step (1) is 5:1, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0055] Embodiment 16: The method of Example 1 is followed, except that in step (1) the MoO 3 The concentration of is 0.01 mmol / mL, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0056] Embodiment 17: The method of Example 1 is followed, except that in step (1) the MoO 3 The concentration of is 0.05 mmol / mL, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0057] Embodiment 18: The method of Example 1 is followed, except that in step (1) the MoO 3 The concentration of is 0.1 mmol / mL, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0058] Embodiment 19: According to the method of Example 1, except that the concentration of PVP in step (1) is 0.0001 mmol / mL, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0059] Embodiment 20: According to the method of Example 1, except that the concentration of PVP in step (1) is 0.0005 mmol / mL, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0060] Embodiment 21: According to the method of Example 1, except that the concentration of PVP in step (1) is 0.001 mmol / mL, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0061] Embodiment 22: According to the method of Example 1, except that the concentration of the metal zinc salt in step (1) is 0.01 mmol / mL, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0062] Embodiment 23: According to the method of Example 1, except that the concentration of the metal zinc salt in step (1) is 0.05 mmol / mL, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0063] Embodiment 24: According to the method of Example 1, except that the concentration of the metal zinc salt in step (1) is 0.1 mmol / mL, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0064] Embodiment 25: According to the method of Example 1, except that the concentration of 2-methylimidazole in methanol in step (2) is 0.1 mmol / mL, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0065] Embodiment 26: According to the method of Example 1, except that the concentration of 2-methylimidazole in methanol in step (2) is 0.5 mmol / mL, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0066] Embodiment 27: According to the method of Example 1, except that the concentration of 2-methylimidazole in methanol in step (2) is 1 mmol / mL, and the rest is the same as Example 1, a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0067] Embodiment 28: According to the method of Example 1, except that the volume ratio of the S1 mixed solution to the S2 clarified solution in step (3) is 2:1, and the rest is the same as Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0068] Embodiment 29: According to the method of Example 1, except that the volume ratio of the S1 mixed solution to the S2 clarified solution in step (3) is 1:2, and the rest is the same as Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0069] Embodiment 30: The method of Example 1 is followed, except that in step (4), the MoO 3 @ZIF-8 precursor material annealing atmosphere is N 2 , the rest are the same as in Example 1, and a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator is obtained.
[0070] Embodiment 31: The method of Example 1 is followed, except that in step (4), the MoO 3 @ZIF-8 precursor material annealing atmosphere is Ar / H 2 (5%), and the rest are the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0071] Embodiment 32: The method of Example 1 is followed, except that in step (4), the MoO 3 The annealing time of the @ZIF-8 precursor material is 1 h, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0072] Embodiment 33: The method of Example 1 is followed, except that in step (4), the MoO 3The annealing time of the @ZIF-8 precursor material is 3 h, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0073] Embodiment 34: The method of Example 1 is followed, except that in step (4), the MoO 3 The annealing time of the @ZIF-8 precursor material is 4 h, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0074] Embodiment 35: The method of Example 1 is followed, except that in step (4), the MoO 3 The annealing time of the @ZIF-8 precursor material is 5 h, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0075] Embodiment 36: The method of Example 1 is followed, except that in step (4), the MoO 3 The annealing temperature of the @ZIF-8 precursor material is 600 °C, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0076] Embodiment 37: The method of Example 1 is followed, except that in step (4), the MoO 3 The annealing temperature of the @ZIF-8 precursor material is 700 °C, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0077] Embodiment 38: The method of Example 1 is followed, except that in step (4), the MoO 3 The annealing temperature of the @ZIF-8 precursor material is 900 °C, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0078] Embodiment 39: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide and selenium powder are mixed in a mass ratio of 1:10, and the rest is the same as in Example 1 to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0079] Embodiment 40: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide and selenium powder are mixed in a mass ratio of 1:5, and the rest is the same as in Example 1 to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0080] Embodiment 41: According to the method of Example 1, except that in step (5), nitrogen-doped carbon-supported molybdenum carbide and selenium powder are mixed in a mass ratio of 1:1, and the rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-supported molybdenum-based lithium-sulfur battery separator.
[0081] Embodiment 42: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide and selenium powder are mixed in a mass ratio of 5:1, and the rest is the same as in Example 1 to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0082] Embodiment 43: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide is mixed with selenium powder in an atmosphere of N2, and the rest is the same as in Example 1 to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0083] Embodiment 44: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-supported molybdenum carbide is mixed with selenium powder in an atmosphere of Ar / H 2 (5%), and the rest are the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0084] Embodiment 45: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide is mixed with selenium powder, and the heat treatment time is 1 h. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0085] Embodiment 46: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide is mixed with selenium powder, and the heat treatment time is 2 h. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0086] Embodiment 47: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide is mixed with selenium powder, and the heat treatment time is 3 h. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0087] Embodiment 48: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide is mixed with selenium powder, and the heat treatment time is 5 h. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0088] Embodiment 49: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide is mixed with selenium powder, and the heat treatment temperature is 300°C. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0089] Embodiment 50: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide is mixed with selenium powder, and the heat treatment temperature is 400°C. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0090] Embodiment 51: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide is mixed with selenium powder, and the heat treatment temperature is 500°C. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0091] Embodiment 52: The method of Example 1 is followed, except that in step (5), nitrogen-doped carbon-loaded molybdenum carbide is mixed with selenium powder, and the heat treatment temperature is 700°C. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0092] Embodiment 53: The method of Example 1 is followed, except that in step (6), 15 mg of selenium-nitrogen co-doped carbon-loaded molybdenum carbide material is mixed with 2 mg of PVDF binder and then added to 90 mg of N-methylpyrrolidone (NMP) solvent and stirred evenly to form a slurry. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0093] Embodiment 54: The method of Example 1 is followed, except that in step (6), 25 mg of selenium-nitrogen co-doped carbon-loaded molybdenum carbide material is mixed with 3 mg of PVDF binder and then added to 110 mg of N-methylpyrrolidone (NMP) solvent and stirred evenly to form a slurry. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0094] Embodiment 55: The method of Example 1 is followed, except that in step (6), 18 mg of selenium-nitrogen co-doped carbon-loaded molybdenum carbide material is mixed with 2.7 mg of PVDF binder and then added to 100 mg of N-methylpyrrolidone (NMP) solvent and stirred evenly to form a slurry. The rest is the same as in Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator.
[0095] Embodiment 56: The method of Example 1 is followed, except that the slurry in step (6) is coated on the surface of the PP diaphragm with a thickness of 10 μm, and the rest is the same as Example 1 to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery diaphragm.
[0096] Embodiment 57: The method of Example 1 is followed, except that the slurry in step (6) is coated on the surface of the PP diaphragm with a thickness of 50 μm, and the rest is the same as Example 1 to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery diaphragm.
[0097] Embodiment 58: The method of Example 1 is followed, except that the slurry in step (6) is coated on the surface of the PP diaphragm with a thickness of 100 μm, and the rest is the same as Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery diaphragm.
[0098] Embodiment 59: The method of Example 1 is followed, except that the modified diaphragm described in step (6) is dried at a temperature of 40°C, and the rest is the same as Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery diaphragm.
[0099] Embodiment 60: The method of Example 1 is followed, except that the modified diaphragm described in step (6) is dried at a temperature of 50°C, and the rest is the same as Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery diaphragm.
[0100] Example 61: The method of Example 1 is followed, except that the modified diaphragm described in step (6) is dried at a temperature of 70°C, and the rest is the same as Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery diaphragm.
[0101] Embodiment 62: The method of Example 1 is followed, except that the modified diaphragm in step (6) is dried at a temperature of 80°C, and the rest is the same as Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery diaphragm.
[0102] Embodiment 63: The method of Example 1 is followed, except that the modified diaphragm in step (6) is dried at a temperature of 90°C, and the rest is the same as Example 1, to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery diaphragm.
[0103] The above content is only for explaining the technical idea of the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a selenium-nitrogen co-doped carbon-supported molybdenum-based lithium-sulfur battery separator, characterized in that: The following steps are involved: S1: dissolving MoO3, polyvinyl pyrrolidone and metal zinc salt in anhydrous methanol and stirring thoroughly to obtain a mixed solution; S2: Dissolve 2-methylimidazole in anhydrous methanol and stir thoroughly to obtain a clear solution; S3: mixing the S1 mixed solution with the S2 clarified solution to obtain a precipitate, washing and drying the precipitate to obtain a MoO3@ZIF-8 precursor material; S4: annealing the MoO3@ZIF-8 precursor material to obtain a nitrogen-doped carbon-loaded molybdenum carbide material; S5: mixing the nitrogen-doped carbon-loaded molybdenum carbide material with selenium powder and subjecting the mixture to heat treatment to obtain a selenium-nitrogen co-doped carbon-loaded molybdenum carbide material; S6: Mix the selenium-nitrogen co-doped carbon-loaded molybdenum carbide material with the PVDF binder, add the mixture into N-methylpyrrolidone solvent, and stir evenly to form a slurry. Apply the slurry on the surface of a commercial polypropylene diaphragm, and obtain a modified battery diaphragm after drying.
2. The method according to claim 1, characterized in that The metal zinc salt in step S1 is zinc nitrate, zinc chloride or zinc sulfate; the mass ratio of MoO3 to polyvinyl pyrrolidone is 1:10~10:1; the mass ratio of MoO3 to metal zinc salt is 1:10~10:1; the mass ratio of polyvinyl pyrrolidone to metal zinc salt is 1:5~5:1; the concentration of MoO3 is 0.01~0.1 mmol / mL; the concentration of polyvinyl pyrrolidone is 0.0001~0.001 mmol / mL; the concentration of metal zinc salt is 0.01~0.1 mmol / mL.
3. The method according to claim 1, characterized in that The concentration of 2-methylimidazole in methanol in step S2 is 0.1-1 mmol / mL.
4. The method according to claim 1, characterized in that: In step S3, the volume ratio of the S1 mixed solution to the S2 clarified solution is 2:1-1:2; the stirring time is 20-45 min, and the washing is performed by washing with water and ethanol for 3-5 times.
5. The method according to claim 1, characterized in that The atmosphere for annealing the MoO3@ZIF-8 precursor material in step S4 is N2 or Ar / H2 mixed gas, the annealing temperature is 600~900 °C, and the annealing time is 1~3h.
6. The method according to claim 1, characterized in that In step 5, the mass ratio of mixing nitrogen-doped carbon-loaded molybdenum carbide and selenium powder is 1:10~10:
1.
7. The method according to claim 1, characterized in that The heat treatment atmosphere in step S5 is N2 or Ar / H2 mixed gas, the heat treatment time is 1~5 h; the heat treatment temperature is 300~700 °C.
8. The method according to claim 1, characterized in that In step S6, the selenium-nitrogen co-doped carbon-loaded molybdenum carbide material is 15-25 mg, the PVDF binder is 2-3 mg, and the N-methylpyrrolidone solvent is 90-110 mg. The slurry is coated on the surface of a commercial polypropylene diaphragm with a thickness of 10-100 μm.
9. The method according to claim 1, characterized in that: The drying temperature in step S6 is 40-90 °C and the drying time is 9-18 h.
10. Application of a selenium-nitrogen co-doped carbon-supported molybdenum-based lithium-sulfur battery separator prepared by the method according to any one of claims 1 to 9, characterized in that: Selenium-nitrogen co-doped carbon-loaded molybdenum-based lithium-sulfur battery separator can be used to make batteries.
Citation Information
Patent Citations
Molybdenum-based nitride / carbide electrocatalyst and preparation method and application thereof
CN114214657A
Preparation method of carbonized Zn-MOF modified diaphragm for lithium-sulfur battery as well as product and application of carbonized Zn-MOF modified diaphragm
CN115939662A
